Countering Sectarianism: The Many Paths, Promises, and Pitfalls of De-sectarianization - Valbjørn, Morten (The review of faith & international affairs, 2020)
It is well known that the "sectarianization" of Middle Eastern politics during the last decade has had many negative effects. In that light, it should come as no surprise that most agree that sectarianism should be countered. However, it turns out that it is anything but clear what we are talking about, when we talk about anti/counter/post/trans/cross/non/multi-sectarianism. Moreover, a shared ambition of countering sectarianism can translate into very different kinds of strategies, some of which are burdened with their own problems or dilemmas, raising the question whether the cure is always better than the disease.